Breast augmentation with an unknown substance. (23rd June 2014) - Ebrahim, Lamya; Morrison, David; Kop, Alan; Taylor, Donna
Abstract : Before the widespread use of silicone implants various foreign substances were injected directly into the breasts. The nature of these materials sometimes remains unknown and can cause various complications requiring surgical intervention. Preoperative diagnostic imaging can help characterise the type and distribution of the injected material, thereby assisting in making decisions regarding treatment. We report a case of breast augmentation with an unknown substance, aiming to highlight some imaging characteristics of different breast augmentation substances.